ANALYZING EXISTENTIAL STRUGGLES AND ABSURD REALITIES IN MUNIR’S UNFETTERED WINGS (Contemporary Journal of Social Science Review, 2024)
Man’s quest for meaning has been the topic of debate among philosophers for ages.  According to existentialism, man derives meaning in life by making choices through his own free will. While absurdism says that there is no meaning at all. Both existentialism and absurdism focus on human actions, free will, freedom of choice, meaninglessness, nothingness, limited freedom, dread, alienation, social isolation, revolt, and pessimism. The present study aims to explore the themes of absurdism and existentialism in Munir’s Unfettered Wings (2018). The study utilized Albert Camus’ theories of absurdism and existentialism to provide an in-depth descriptive qualitative analysis of the existential struggles and absurd realities faced by the main characters of the selected novel. The research concluded that Munir’s Unfettered Wings consists of various aspects of absurdism and existentialism. As the main characters continuously face the absurd realities of life but regardless of these absurdities, they often attempt to create meaning for their existence.